Applying Merton's valuation adjustment for incomplete information … and do you need to?. Issue 1 (19th November 2019) - O'Brien, Thomas
Abstract : Purpose: The purpose of this paper is to offer a "how to" guide for applying Merton's (1987) valuation adjustment for incomplete information, which depends on market capitalization, idiosyncratic risk and extent of investor ownership. Design/methodology/approach: The paper illustrates Bodnaruk and Ostberg's (2009) formula for Merton's adjustment, and presents some example empirical estimates of the adjustment for some US stocks. Findings: The adjustment estimates are material for many example stocks, particularly volatile stocks with a low percentage of shares held by institutional funds. However, the adjustment estimates are modest for many other stocks, including some smaller cap. stocks. Research limitations/implications: Measuring the model's inputs requires using some judgment, particularly regarding the investor ownership variable. The paper will hopefully help stimulate useful empirical research on adjustment estimates and on best practices for applying the model. Practical implications: The paper may encourage more use of the incomplete-information adjustment in practice, which should lead to improved discount rate estimates in valuation analyses. Originality/value: No other "bridge the gap" coverage of the incomplete-information adjustment is available in textbooks or the applied literature.